2015
DOI: 10.1007/s10833-015-9250-8
|View full text |Cite
|
Sign up to set email alerts
|

Redefining high performance in Northern Ireland: Deeper learning and twenty-first century skills meet high stakes accountability

Abstract: This study examined four secondary schools in Northern Ireland serving a significant percentage of low income families: two schools from the 'Maintained' (de-facto Catholic) sector, one school from the 'Controlled' (de-facto Protestant) sector, and one school from the 'Integrated' (mixed faith) sector. The objective was to identify when and how the schools fostered higher level cognitive skills, interpersonal skills and intrapersonal skills, known collectively in the literature as twenty-first century learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The researcher, from the United States, took up residence in Northern Ireland for three months in the fall of 2017. The researcher had previously lived in Northern Ireland for five months in 2013-2014 while conducting a previous study there (Nehring and Szczesiul, 2015). The researcher made 37 part-or full-day visits to the four schools between early September and late November to observe classes, interview administrators and teachers, and conduct student focus groups.…”
Section: Below Summarizes Student Demographics At Meadow and Mountainmentioning
confidence: 99%
See 1 more Smart Citation
“…The researcher, from the United States, took up residence in Northern Ireland for three months in the fall of 2017. The researcher had previously lived in Northern Ireland for five months in 2013-2014 while conducting a previous study there (Nehring and Szczesiul, 2015). The researcher made 37 part-or full-day visits to the four schools between early September and late November to observe classes, interview administrators and teachers, and conduct student focus groups.…”
Section: Below Summarizes Student Demographics At Meadow and Mountainmentioning
confidence: 99%
“…Studies of schooling in Northern Ireland have examined the benefits and challenges of schoolbased integration of students from culturally diverse backgrounds-principally Catholic and Protestant (Hughes et al, 2012;Loader, 2017;McDaid, 2015;Nehring and Szczesiul, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Possible conflicts between the new school profile and these established traditions and practices may create tensions and constrain teacher autonomy, and previous research has suggested that school profiles and national evaluations can both limit individual autonomy (Heinrich 2015;Hopmann 2003;Lundström 2015;Lundström and Parding 2011;Wermke and Forsberg 2017). Research has also pointed out similar tensions between high-stakes subject-focused testing and cross-curricular non-subject goals such as twentifirst-century skills, creativity and innovation (Cachia et al 2010;Collard and Looney 2014;Erss et al 2016;Looney 2009;Maustethagen 2013;Nehring and Szczesiul 2015;Sahlberg 2010Sahlberg , 2011. In such situations, teachers might find themselves between two different logics of education: one driven by accountability based on high-stakes testing and a second driven by a collegial vison of socially and morally responsible education (e.g.…”
Section: Introductionmentioning
confidence: 99%